Translation and cultural adaptation of the Self-Talk Questionnaire for sports (S-TQ) into Brazilian Portuguese - Thiago Siqueira Paiva de Souza; Luiz Carlos Serramo Lopez (Colégio Brasileiro de Ciências do Esporte, 2020)
ABSTRACT The purpose of this study was to translate and culturally adapt the Self-Talk Questionnaire for Sports (S-TQ). The process of its translation and cultural adaptation to the Brazilian Portuguese language was carried out in 4 stages: translation, backtranslation, comprehension test with specialists, and comprehension test with the target audience. After the independent translation process, the two versions were compared, and it was found that translation equality was reached for 93.59% of the text and 85.83% after the backtranslation process. In the subsequent steps, the S-TQ version was considered to have a good level of understanding, and it maintained greater than 90% in this regard. Therefore, it is concluded that the S-TQ for sports is suitable for scale validation processes.